Commodification of Popular Culture as a tool of Consumerism in Seventeen World Tour 'Right Here' in Jakarta - Khairunnisa Devani Aqtus Permana Putri (Universitas Lambung Mangkurat, 2025)
Popular culture is one of the elements that cannot be separated from the layers of society. Popular culture raises the principle of cultural proximity. Various kinds of popular culture that the public can accept are diverse, including K-pop through the Seventeen World Tour 'Right Here' activities in the Jakarta concert series. This research looks at how popular culture, namely music, becomes a tool of consumerism for fans. This research uses quantitative methods to study popular culture through various sources, such as social media and electronic news. This concert series is one of the representations of popular culture with broad fan access. Consumerism shapes identity and interaction between fans, causing popular culture to continue to grow and creating acts of consumerism and active participation by fans to fulfill their fans' deep needs and desires.